Draft Tenth Five Year Plan 2002-07 and Annual Plan 2002-03 - Planning Commission (Planning Commission, 2002)
"The Union Territory of Pondicherry consists of four regions, namely, Pondicherry, Karaikal, Mahe and Yanam lying geographically isolated from one another. Pondicherry region which is on the east coast, about 162 kms. south of Chennai is the largest of these and consists of 12 scattered areas interspersed with enclaves of Villupuram district and Cuddalore District of Tamilnadu. Karaikal region is about 150 Kms. south of Pondicherry and it is surrounded by Nagapattinam District of Tamilnadu. Yanam region is located about 840 kms. north east of Pondicherry near Kakinada in Andhra Pradesh. Mahe region lies almost parallel to Pondicherry 653 kms. away on the west coast near Tellicherry in Kerala. Area and Population The Union Territory of Pondicherry is 492 sq.kms. in area and has a population of 9,73,829 consisting of 4,86,705 males and 4,87,124 females according to 2001 census. The region-wise breakup is as follows"
Special Component Plan